Financial markets, banking, and monetary policy - Simpson, Thomas D., 1942- (Wiley, 2014)
"The current financial model has focused on money as a unique asset that is produced exclusively by commercial banks, and regulated by central banks to achieve their macroeconomic goals. However, as financial systems have evolved in the United States and elsewhere around the globe, what constitutes money has become blurred and such monetary aggregates have become highly unreliable and discarded guides to policy. As a result, central banks have had to turn to a very different approach for achieving macroeconomic goals. This approach instead focuses on influencing the prices of a broad spectrum of financial assets, and thereby the spending behavior of businesses and consumers. They do so by relying on their control over the short-term policy interest rate and its influence on the core element of all asset prices through the term structure of interest rates. This book will create a better understanding of that monetary policy so both students and professionals can get a solid understanding of this term structure relationship and how it works throughout the financial system."--